2021
DOI: 10.1371/journal.pone.0255983
|View full text |Cite
|
Sign up to set email alerts
|

Enlarged extracellular vesicles are a negative prognostic factor in patients undergoing TACE for primary or secondary liver cancer–a case series

Abstract: Background Transarterial chemoembolization (TACE) has evolved as a standard treatment option in patients with intermediate stage, unresectable HCC [Barcelona Clinic Liver Cancer (BCLC) stage B] as well as in patients with liver metastases, when surgery or systemic therapy is considered not appropriate. Concentration and sizes of extracellular vesicles (EVs) recently emerged as novel diagnostic and prognostic biomarkers in patients with liver cancer, but no data on its prognostic relevance in the context of TAC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…Instead, no differences were observed between HCV patients and healthy controls as regarding the concentration of EVs ( Figure 1 C,D). These results are in agreement with previous reports showing that EVs sizes rather than EVs concentrations are increased in liver failure patients and correlate with prognosis [ 24 , 25 , 26 , 27 ].…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Instead, no differences were observed between HCV patients and healthy controls as regarding the concentration of EVs ( Figure 1 C,D). These results are in agreement with previous reports showing that EVs sizes rather than EVs concentrations are increased in liver failure patients and correlate with prognosis [ 24 , 25 , 26 , 27 ].…”
Section: Resultssupporting
confidence: 93%
“…The same applies to chronic viral hepatitis B, where both large [ 50 ] and small EVs [ 51 , 52 ] were reported. In any case, it is noteworthy that sizes rather than the concentrations of EVs were found to be correlated with the prognosis of such different conditions as acute liver failure [ 25 ], cirrhosis [ 26 ], and/or HCC [ 27 ], providing evidence for their previously unrecognized role as biomarkers also in this specific context.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, the current work is the first to report a quantitative analysis of the distribution of EVs in patients with chronic liver disease, and it supports the conclusion that analysis of EVs in crude serum might provide prognostic or diagnostic information. In this regard, we have recently shown that EVs sizes represent a novel prognostic marker in patients receiving transarterial chemoembolization (TACE) for primary and secondary hepatic malignancies [34].…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, the presented work is the first study investigating EVs in patients with chronic liver diseases, and it supports the conclusion that analysis of EVs in crude serum might provide prognostic or diagnostic information. In this regard, we have recently shown that EVs sizes represent a novel prognostic marker in patients receiving transarterial chemoembolization (TACE) for primary and secondary hepatic malignancies [38].…”
Section: Discussionmentioning
confidence: 99%